Dominasi atau Persetujuan? Hegemoni Keluarga dalam Praktik Perjodohan pada Cerita Romansa Jodho Pilihan Bapak - Hafit Yudya Kristalianto; Suwardi Endraswara; Doni Dwi Hartanto (Faculty of Languages and Arts, Universitas Negeri Padang, 2026)
Javanese romance stories often portray socio-cultural issues within society, including the practice of arranged marriage. In Javanese culture, family involvement in determining a child’s spouse remains significant, particularly for women, as considerations of social status, family reputation, and economic stability frequently shape marital decisions. This phenomenon reflects the operation of family hegemony through the internalization of cultural values and social consent. This study examines the forms of family hegemony and the female character’s responses to arranged marriage in the romance story Jodho Pilihan Bapak. Using a qualitative approach, this research applies content analysis within the frameworks of sociology of literature and Gramsci’s theory of hegemony. The data consist of narrative passages and dialogues that represent family power relations and the female character’s responses. The findings reveal that family hegemony operates through moral pressure, the legitimization of social and economic values, and parental authority in determining a life partner. Although the female character initially experiences inner conflict, she gradually negotiates and eventually accepts the arranged marriage. These findings suggest that arranged marriage in Javanese romance literature functions not only as a cultural representation but also as a mechanism through which family hegemony shapes individual consent. Furthermore, the study highlights the relevance of literary texts as critical material for Javanese literature learning.